PEMANFAATAN UMBI GADUNG DAN SERAT DAUN NANAS UNTUK PEMBUATAN PLASTIK BIODEGRADABLE - Yuniwati, Murni (Jurnal Teknologi Technoscientia, 2017)
Plastic wastes are increasingly causing serious problems for the community. This can be overcome with various methode, one of them by replacing the use of conventional plastics with biodegradable plastic. Biodegradable plastic has been produced, but its strength is still very less compared to conventional plastics. Therefore, there needs to be innovation in making stronger biodegradable plastic. This research tries to utilize starch of gadung  as raw material of biodegradable plastics and as a reinforcement used fiber of pineapple leaf  and glycerin as platilizer. Stages of making biodegradable plastics include the preparation (the manufacture of gadung starch, and fiber of pineapple leaf), followed by plastic manufacturing process by mixing the gadung starch, acetic acid, glycerin and fiber of pineapple leaf, then stirring and heating for a certain time, And the last stage is the printing and drying of the results. The research was conducted on  temperature, time of process , stirring speed, and the weight  ratio of gadung starch to fiber of pineapple leaf, to know the optimal process condition to obtain plastic with big tensile strength. Using 10 grams gadung starch, 100 mL of 0.5% acetic acid and 2.5 mL glycerin obtained optimum condition using 80oC, 90 minutes, 300 rpm stirring speed and weight  ratio of gadung starch to fiber of pineapple leaf is 10 : 1. By using the condition obtained by plastic with a tensile strength of 3.87 MPa. The FT-IR (Fourier Transform Infra Red) test on the plastics of this study shows that the plastic of this research is biodegradable plastic